2016
DOI: 10.1093/cvr/cvw218
|View full text |Cite
|
Sign up to set email alerts
|

TSP1–CD47 signaling is upregulated in clinical pulmonary hypertension and contributes to pulmonary arterial vasculopathy and dysfunction

Abstract: In pre-clinical models of PH CD47 targets cMyc to increase ET-1 signaling. In clinical PH TSP1-CD47 is upregulated, and in both, contributes to pulmonary arterial vasculopathy and dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 71 publications
7
79
0
Order By: Relevance
“…Prior studies have shown that TSP-1 is necessary for hypoxia-induced PH171819, but the role of TSP-1 remains unclear: as a large, multimeric protein, TSP-1 can also interact with other proteins including its receptors CD36 and CD47, which could mediate PH development20. Other studies have suggested TSP-1 may regulate NO and endothelin-1 signalling via interactions with CD47 (refs 16, 18, 21). TSP-1 can alter the vascular matrix by disrupting endothelial cell junctions and promoting migration of cells including fibroblasts and smooth muscle cells17.…”
mentioning
confidence: 99%
“…Prior studies have shown that TSP-1 is necessary for hypoxia-induced PH171819, but the role of TSP-1 remains unclear: as a large, multimeric protein, TSP-1 can also interact with other proteins including its receptors CD36 and CD47, which could mediate PH development20. Other studies have suggested TSP-1 may regulate NO and endothelin-1 signalling via interactions with CD47 (refs 16, 18, 21). TSP-1 can alter the vascular matrix by disrupting endothelial cell junctions and promoting migration of cells including fibroblasts and smooth muscle cells17.…”
mentioning
confidence: 99%
“…In these experiments, effects were reported only in vessels from female animals (182). TSP1 also inhibited NO-mediated vasodilation of pulmonary arterial rings from mice as well as rats (214), indicating that TSP1 limits vasodilation of the systemic and pulmonary vasculature. It remains to be seen whether the pulmonary arterial effects of TSP1 are secondary to increased ROS.…”
Section: B Tsp1 and Ros Signaling In Vascular And Renal Cellsmentioning
confidence: 78%
“…In a small longitudinal (n = 8) cohort, plasma TSP1 levels increased coincident with the development of scleroderma-associated PH (117). TSP1 and CD47 protein are increased in lungs and distal pulmonary arteries from PH patients compared with samples from non-PH controls (214). Bias-reduced logistic regression analysis found significant positive relationships ( p < 0.05) between parenchymal and pulmonary arterial TSP1 protein expression and PH.…”
Section: A Redox Signaling In Stem Cellsmentioning
confidence: 94%
See 2 more Smart Citations